Readability analysis of prose texts in the Malaysian lower secondary schools (IR) - Revathi Gopal (2018)
This research aims to analyze the readability of prose texts used for Malaysian lower secondary school students. The research involves both the quantitative and qualitative research methods in collecting data. The quantitative research methods are used to gauge readability level of the texts used and also students’ views on reading the literary texts prescribed focusing on text-reader factors which are i) cultural familiarity of the texts, ii) physical features of the texts, iii) students’ interest and motivation and iv) the preferred prose texts. The qualitative research method investigates the text-reader factors which affect students’ reading comprehension and students’ strengths and weaknesses in understanding the prose prescribed. Samples comprised randomly selected lower secondary school students from secondary schools in Perak. A total of 450 respondents and 18 participants were involved in the research. Data collection techniques include four readability formulas, a cross-sectional survey, interviews, and retelling procedures. Data collected were analyzed using descriptive statistical analysis, thematic analysis, in-depth procedures and judging richness of retellings. Also included are four online readability formulas to analyze the readability level of the prose texts used in schools. The findings show that the prose forms were below students’ age level and the physical features of the prose texts could be improved to enhance reading interest. The results of the retellings analysis suggest that the prose forms are readable and are within students’ comprehension ability level. The implication of the research however indicates that future selection of prose texts prescribed for use in schools should meet the needs and age level of the students and those which best fits students’ reading interest.